Monitoring training loads in handcycling - Preparing for Rio 2016 - Zeller, S.; Abel, T.; Strüder, H. K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Aim: Scientific literature containing training load monitoring in Paralympic sports is lacking. The aim of the present study was to analyze training loads in handcycling for the first time during a full competitive season of a multiple Paralympic medalist. Methods: At the beginning of this observation in 11/2014 the featured handcyclist was 54 years old (classification: WH5, height: 1.78 m, body mass: 68.0 kg, body fat: 12.8 %). As a member of the German paracycling national team she won four medals in the 2008 and 2012 Paralympic Games. Aiming towards the 2016 Paralympic Games this study is focusing on the preparation and the competitive period of the 2015 season. Using a SRM-Powermeter every training session was recorded from 11/2014 to 09/2015. At the beginning of the observation and in may 2015 laboratory testing were conducted to determine training intensities. Training intensity was analyzed according to the five-zone intensity scale (Seiler, 2010) like shown in table 1. In addition to this scale the model of three intensity zones (1: below the individual lactate threshold (ILT), 2: between the ILT and the onset of blood lactate accumulation (OBLA), and 3: above the OBLA) was used to compare the present results with general results in the literature (Seiler, 2010). Results: The athlete completed 186 handcycling training sessions in 382:28 hours, covered a distance of 8640.96 km, climbed 35611.0 m and burned around 145000 kj during the investigation. The intensity distribution according to the five- and three-zone intensity scale is shown. Conclusions: Maintaining a high fitness level throughout the season was important to collect points for the qualification of the 2016 Paralympic Games. This aim was reached by winning every worldcup time-trial of the 2015 season. The analysis of the training intensity distribution shows a tendency to a greater volume in zone 2 than recommended in the literature (Esteve-Lanao et al., 2005; Seiler, 2010; Stöggl & Sperlich, 2015). Therefore, a room for improvement for the upcoming Paralympic season was found.